Model of a Monopulse Radar Tracking System for Student Laboratory - N. Majurec (Radioengineering, 2007)
Development, construction and testing of a student laboratory model of the radar system that can be used for monopulse tracking is described. The laboratory model is simple and can be assembled from the existing equipment while the missing parts can be manufactured in a basically equipped RF electronics workshop. The laboratory model is used for student laboratory exercises as a part of a basic course on radar systems. The system is based on a Î£-Î hybrid for processing signals obtained from two antennas. The composition of the model is described. Student exercises and measurements on the model are proposed. Alternative instruments which can be used in the model are considered. Possible improvements of the model are discussed.